Diagnostic Lessons from a Complex Case of Postintestinal Transplantation Enteropathy - Cian Wade; Philip Allan; Elena Collantes; Srikanth R. Reddy; Peter J. Friend; Georgios Vrakas (Case Reports in Transplantation)
Recent advances in the field of intestinal transplantation have been mitigated by the incidence of allograft rejection. In such events, early identification and appropriate timing of antirejection therapy are crucial in retaining graft function. We present the case of a patient who suffered severe postintestinal transplantation allograft enteropathy, primarily characterized by extensive mucosal ulcerations, and was refractory to all conventional therapy. This progressed as chronic rejection; however crucially this was not definitively diagnosed until allograft function had irreversibly diminished. We argue that the difficulties encountered in this case can be attributed to the inability of our current array of investigative studies and diagnostic guidelines to provide adequate clinical guidance. This case illustrates the importance of developing reliable and specific markers for guiding the diagnosis of rejection and the use of antirejection therapeutics in this rapidly evolving field of transplant surgery.